Airfield pavement design with cold recycled materials - Lacalle Jiménez, Helena Isabel (2017)
The UK has adopted the concept of sustainable development and the construction industry is playing a key role in improving the efficient use of materials. The aim is to minimise the waste generated and maximise quantities of materials reused or recycled, minimising raw material consumption. Using Reclaimed asphalt pavement (RAP) is a rehabilitation technique which involves recycling materials from asphalt layers that have already been in service. This reduces the use of new bitumen and aggregates and avoids disposal. However, UK pavements constructed prior to 1980 or surfaced in the late 1980’s may contain tar, a carcinogenic substance that cannot be reheated and, therefore, cannot be recycled into hot mix asphalt (HMA). Recycling these pavements into unbound materials is also prohibited; consequently, disposal or cold recycling are the two available options. Cold recycling of asphalt is a proven technique that reduces material disposal and raw material and energy consumption. The reduction in energy consumption is largely achieved by avoiding aggregate drying and mixing of the material at ambient temperature. In this sense, using cold recycled bound materials (CRBMs) becomes the most economic and sustainable option. However, despite the increasingly common use of CRBM in roads, the specifications for the use of these materials in airfields are under-developed and there is no guidance to ensure that pavement design with these materials is trustworthy. This is the reason why this Thesis focuses on airfield pavement design with CRBM. The aim of this investigation is to develop a design methodology to use CRBMs in airfield pavements. For this purpose, the objectives were to review past experience on performance of these materials, measure and analyse the effect of key variables on performance to establish material limitations and develop a design methodology, proposing design guidance for airport authorities and practitioners. To achieve the project aims and objectives, a literature review was carried out focusing on pavement engineering, airfield pavement design and CRBM. The objective was to gain sufficient knowledge on key areas to conduct the research. Based on this literature review it was decided to use foamed bitumen as the cold technology and Kenlayer as pavement analytical design software. It was also found that the current design methodology for using CRBM in airfields is to conservatively equate material properties to those of a HMA commonly used in airfield base course (HDM50). Therefore, this practise should be analysed to decide if it is correct or if it can be improved. Subsequently, a laboratory programme was established to analyse CRBM mechanical properties and, therefore, understand the material’s behaviour and performance under cyclic loading. RAP, fly ash, cement and foamed bitumen were used to manufacture laboratory specimens, compacted with a gyratory compactor. These specimens were tested to analyse densities, air voids, stiffness, strength, permanent deformation and fatigue. For developing a new design methodology, Kenlayer was used to analyse strains and stresses within the airfield pavement. The first step was to ascertain Kenlayer adequacy and establish inputs related to loading, traffic and subgrade condition. For this purpose, 96 case studies were analysed with HMA, with different aircraft types, traffic and subgrade conditions. These cases were compared to those of a well-established airfield design guide, namely DMG 27. Then the software could be used to model pavements containing CRBM and with the knowledge gained in the laboratory about its behaviour, establish layer thicknesses to bear traffic during the pavement design life. With the results obtained from the laboratory investigation it was concluded that CRBM mixes have acceptable properties for use in airfield pavements. Resistance to permanent deformation, fatigue, temperature susceptibility and durability results show that these materials give reasonable performance; however, they differ from conventional hot mixes. Thus, current practice can be improved, justifying the need for design guidance for using CRBM in airfields. As fatigue is one of the main failure modes in asphalt mixtures and flexible pavements, a deeper study into fatigue behaviour of CRBM was carried out using Indirect Tensile Fatigue Tests (ITFT) in strain control mode and Wheel Track Test (WTT). The results showed different failure mechanisms for CRBM from those of HMA; thus, a new failure criterion was established. In HMA the failure criterion of 50% stiffness reduction is related to the appearance of macro cracks. CRBM develops dispersed micro-cracking that lowers the mixture stiffness without producing macro cracks until late in the material’s life. Macro cracks only tend to appear at 70% stiffness reduction; therefore, this was established as new failure criterion for CRBM. Once CRBM properties were defined, the pavement structure could be modelled. The results obtained from HMA modelling showed that the software and the inputs selected were appropriate for this investigation. Then the HMA base properties were substituted with CRBM properties obtained in the laboratory. The results showed that DMG 27, Chart 7, can be used for designing airfield pavements using CRBM increasing the base thickness by 9%, with a minimum Dry Lean Concrete (DLC) layer of 150 mm. A deterioration analysis was also carried out with the design software. In this case the aim was to analyse how strains distribute within the CRBM layer and how this affects the pavement life. With these analysis, it was highlighted how different CRBM behaves compared to HMA. Strains distributed linearly within the HMA layer; however, this does not happen with the CRBM. Moreover, this analysis showed how fatigue data can be used to obtain a more accurate pavement life taking into account different strain levels. Nevertheless, the study carried out here is based on laboratory performance of one type of CRBM. There is need for further investigation to establish a relationship between fatigue behaviour in the laboratory and the field and confirm how micro cracking affects the bearing capacity of the CRBM layer, establishing shift factors to optimise CRBM layer thickness. Moreover, the laboratory study has been carried out analysing CRBM in the same way as HMA; therefore, further study is needed to analyse the adequacy of the testing methodology. Also, modelling has been done comparing one CRBM to one HMA, namely HDM50; therefore, further investigation is needed to open the model to other HMA. Consequently, the design guidance presented here is a first step towards an airfield pavement design guide and further study is needed to optimise it.